VD_FINDINFO HC / 2022 / 261 vom 7. April 2022 - VD Tribunal cantonal (2022)
CAPACITÉ D'ÊTRE PARTIE, RÉSILIATION IMMÉDIATE, CONTRAT DE TRAVAIL, INDEMNITÉEN GÉNÉRAL | 337c al. 3 CO, 59 al. 2 let. c CPC (CH)